Mapping and Analysis of Exit Strategy Research: A Bibliometrics and Systematic Review - Alireza Valipour; Ali Heidari; Mohammad Ali Shahhosseini; Asadollah Kordnaiej (‫مدیریت بازرگانی)
Objective Business exit strategies are fundamental to ensuring a company's long-term viability. Despite their critical role, this area of research has been surprisingly understudied. This knowledge gap can leave companies unprepared to navigate the complexities of exiting a market or business venture. To bridge this critical knowledge gap, our study conducts a systematic literature review, analyzing research findings from the past three decades (1990-2022). By synthesizing key findings, we aim to provide a comprehensive overview of current research trends in business exit strategies. This analysis will not only offer valuable insights into existing knowledge but also identify potential gaps and opportunities for future exploration. By understanding the research landscape, we can pave the way for more informed decision-making and successful business exit strategies.